(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
According to modern anthropologists, the program of phylogenetic development of mankind’s and the ontogenetic development of the individual presupposes a certain necessary adaptation, which is conditioned by virtual reality, the latest technology, high technologies, online communication models, virtual organization leisure time. Without the mentioned points the socialization of the person is impossible. According to digital pedagogical anthropologists, it is time to talk about the computer socialization of the learner, as a component of the general human socialization process, to review the object of study of pedagogical anthropology, and the corresponding educational paradigm. The problem. The rapid development of the digital pedagogical anthropological field on the basis of techno anthropology leads to the development of a new specialization of digital pedagogical anthropologist. The professional must have appropriate professional competencies, ensure the computer socialization of the learners, developing the virtual individual development maps of the learner. The novelty of the research. The research provision is substantiated, according to which the rapid development of digital pedagogical anthropological direction presupposes the formation of a new specialization - digital pedagogical anthropologists, who, having relevant professional competencies, will carry out computer socialization of students in the context of general socialization. Digital pedagogical anthropologists predict that the object of study of pedagogical anthropology will be the cyber human, and the subject - computer socialization. 180 The professional activity of a digital pedagogical anthropologist should be developed in two main directions: social-humanistic and free-humanistic. The activities should be based on two main principles: 1․complete research 2․principles of recording changes and regular analysis during the development process. The conditions for developing the professional competencies of a digital pedagogical anthropologist are: 1. Transition from non-formal practical activity to formal professional theoretical-practical activity 2. With appropriate qualification: training of digital pedagogical anthropologists 3. Specification of the fields of activity of digital pedagogical anthropologists, 4. Clarification of the functions of professional activity, 5. Definition of rights and responsibilities of digital pedagogical anthropologists on the basis of relevant normative documents 6. Use by digital educators-anthropologists of a range of valid pedagogical tools, 7. Certification of digital educators-anthropologists in accordance with the improvement of professional competencies.